2022
DOI: 10.3390/ijerph191912594
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Public Sentiment under the Background of Major Emergencies—Taking the Shanghai Epidemic as an Example

Abstract: The occurrence of major health events can have a significant impact on public mood and mental health. In this study, we selected Shanghai during the 2019 novel coronavirus pandemic as a case study and Weibo texts as the data source. The ERNIE pre-training model was used to classify the text data into five emotional categories: gratitude, confidence, sadness, anger, and no emotion. The changes in public sentiment and potential influencing factors were analyzed with the emotional sequence diagram method. We also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Initially, due to the common fear of falling ill with an unknown, new disease, the introduction of restrictions met with great approval and understanding which, as they were maintained for longer, decreased and caused various negative emotional reactions (powerlessness, discouragement, sadness, anger, fear, anxiety, etc. ), which often translated into denying the danger of the pandemic, undermining the sense of the introduced restrictions, rebellion in the form of deliberate non-compliance with them or spreading conspiracy theories about the pandemic or coronavirus vaccines ( Czeisler et al, 2020 ; Hagen et al, 2022 ; Kim et al, 2022 ; Szuster et al, 2022 ; Turska-Kawa and Pilch, 2022 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Initially, due to the common fear of falling ill with an unknown, new disease, the introduction of restrictions met with great approval and understanding which, as they were maintained for longer, decreased and caused various negative emotional reactions (powerlessness, discouragement, sadness, anger, fear, anxiety, etc. ), which often translated into denying the danger of the pandemic, undermining the sense of the introduced restrictions, rebellion in the form of deliberate non-compliance with them or spreading conspiracy theories about the pandemic or coronavirus vaccines ( Czeisler et al, 2020 ; Hagen et al, 2022 ; Kim et al, 2022 ; Szuster et al, 2022 ; Turska-Kawa and Pilch, 2022 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that experiencing traumatic events might put individuals at risk for a variety of short-term and long-term mental health problems (Bell & Folkerth, 2016 ; Gillies et al, 2016 ; Gulliver et al, 2021 ; Norris et al, 2002 ; Zhang et al, 2022 ). Traumatic events can be caused by various natural disasters, accident disasters, public health accidents and social security events (Cushing & Braun, 2018 ).…”
mentioning
confidence: 99%